Social Media Motivations Scale (SMM-S): Measure Adaptation and Predictors - Fardin Pedruzzi, Pâmela (2021)
Antecedents: Motivation for using social networks helps to understand the online behaviors of the adult population and can be a relevant predictor of several variables, considering its common usage on a daily routine. Objective: This article aimed to seek evidence of validity and accuracy for the Social Media Motivations Scale (SMM-S) in the Brazilian context and understand its relationship with personality and life satisfaction. Method: The research was carried out in two stages, with 600 adults in each one, users of online social networks. In both samples, most were women with higher education, from all Brazilian regions and pointed Instagram as their favorite online service. Results: Results indicated that the adapted version of the Social Media Motivations Scale presented indicators of validity and reliability for a structure of four dimensions: Freedom in Social Networks, Routine in Social Networks, Identity in Social Networks and Social Maintenance. Correlations with life satisfaction and personality revealed evidence of convergent validity. Conclusion: The instrument showed validity psychometric evidences for the Brazilian context. The article presents a discussion of the motivations for social networks usage in different contexts. Authorship contribution All authors participated in the conception and design of the work, data acquisition, analysis and interpretation of data, writing of the manuscript, and critical review of the manuscript.